2001
DOI: 10.1016/s0893-133x(01)00297-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Standardized Extracts of St. John's Wort on the Single-Unit Activity of Serotonergic Dorsal Raphe Neurons in Awake Cats Comparisons with Fluoxetine and Sertraline

Abstract: St. John's wort, p.o.) and i.v.). Both preparations were found to have no effect on neuronal activity. This contrasts sharply with the action of fluoxetine and sertraline (2 mg/kg, p.o.) 8-hydroxy-2-(di-n-propylamino)tetralin (10 g/kg, i.v.). Overall, these -hydroxytryptamine (serotonin); ElectrophysiologyThe medicinal plant Hypericum perforatum L., commonly known as St. John's wort, appears to be an effective antidepressant with few side effects (Hippius 1998;Wheatley 1998;Vitiello 1999). In Germany, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Herbal extracts have recently been reported as complementary therapies for antidepressant purposes, and this type of treatment is expected to prevent onset of mood disorders and regulate serotonin reuptake activity [35, 36]. However, these alternative remedies are limited in the treatment of severe depression [9, 37]. In the present study, we examined TPH-1 and TPH-2 mRNA expression levels in RBL-2H3 cells after treatment with 0, 50, and 100 μ g/mL of TTK.…”
Section: Discussionmentioning
confidence: 99%
“…Herbal extracts have recently been reported as complementary therapies for antidepressant purposes, and this type of treatment is expected to prevent onset of mood disorders and regulate serotonin reuptake activity [35, 36]. However, these alternative remedies are limited in the treatment of severe depression [9, 37]. In the present study, we examined TPH-1 and TPH-2 mRNA expression levels in RBL-2H3 cells after treatment with 0, 50, and 100 μ g/mL of TTK.…”
Section: Discussionmentioning
confidence: 99%
“…Another study (Fornal et al, 2001) found no effect of SJW extracts on the firing rate of 5-HT neurons in the cat dorsal raphe, which is inhibited by compounds such as the 5-HT reuptake inhibitors, that increase the synaptic availability of 5-HT. At variance with these results, a ''push-pull superfusion'' study in the rat locus coeruleus showed that systemic hyperforin induced a lasting (>5 h) and marked (100-200%) increase in the extracellular concentrations of 5-HT, but not 5-HIAA (Kaehler et al, 1999).…”
Section: Serotoninergic Systemmentioning
confidence: 98%
“…There are several possibilities for this discrepancy. One is that the stimulation rate used by Ito and colleagues may be outside the physiological firing range for DR neurons, which typically fire at ~3 Hz during quiet wake, but were stimulated at 20 Hz optogenetically 34 . Another possibility is that Ito et al used Tph-Chr2 mice that express channelrhodopsin in all serotonergic neurons.…”
Section: Discussionmentioning
confidence: 99%